Alteração da fertilidade do solo como indicador do processo de antropização e presença de atividades não agrícolas no assentamento rural Horto Aimorés, municípios de Bauru e Pederneiras/SP =: Change of soil fertility as an indicator of the anthropization process and presence of non agricultural activities at the rural settlement Horto Aimorés, cities of Bauru and Pederneiras/ SP - Zaher, Camila Al [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The pedosphere, from an ecological point of view, performs an essential function for the maintenance of life, if thinking in the unrestricted meaning of the word. In a geographic context, it is in the soil where the process of production of space materializes itself, whether it is urban or rural. In rural areas, the soil has been heavily degraded. The soil usually is degraded by inadequate practices of agricultural holdings. The pedosphere is predominantly based on the capitalist logic of the production, on the large estates, in monoculture and agribusiness. The soil degradation process was accelerated since 1960s with the modernization of agriculture that adopted new cultivate techniques and soil management, such as the use of heavy equipment and chemical inputs (fertilizers) in order to increase productivity. However, without proper planning, these practices may result in chemical soil degradation, physical soil degradation and mostly results in social and economic fragmentation of peasant agriculture. We need to considerate that the so-called modernization proved to be absolutely selective. In this context was formed the rural settlement Horto Aimorés. It is located on the center of São Paulo state between the cities of Bauru and Pederneiras. This settlement was divided in two areas named Gleba I and Gleba II. The Gleba I had 165 plots distributed over 5,262 ha. In this settlement some areas were identified with soil degradation such as compaction, erosion, loss of fertility, among others. These degradations impaired the agricultural production and consequently the maintenance of the settled families and in these situations are noted the presence of non-agricultural activities...

Sob o ponto de vista ecológico, a pedosfera desempenha funções essenciais à manutenção da vida, num sentido irrestrito da palavra. Inserido no contexto geográfico, é também no solo que o processo de produção do espaço se materializa, seja ele urbano ou rural. No meio rural, esse recurso vem sendo intensamente depauperado, via de regra, devido às práticas inadequadas de exploração agrícola, predominantemente pautada na lógica capitalista de produção, calcada no latifúndio, na monocultura e no agronegócio. Esse processo foi acelerado a partir da década 1960, com a chamada modernização da agricultura, que adotou novas técnicas de cultivo e manejo dos solos, como o uso de equipamentos pesados e insumos químicos: adubos e fertilizantes com o objetivo de aumentar a produtividade. No entanto, sem o planejamento adequado, essas práticas podem resultar na degradação química e física dos solos e, sobretudo, na fragmentação social e econômica da agricultura camponesa, tendo em vista o fato de que a dita modernização se mostrou absolutamente seletiva. Nesse contexto encontra-se o assentamento rural Horto Aimorés, localizado entre os municípios de Bauru e Pederneiras, centro-oeste do estado de São Paulo. O referido assentamento está dividido em duas Glebas, I e II. A Gleba I, analisada nesta pesquisa, possui 165 lotes distribuídos em 5.262 ha. No assentamento identificam-se quadros de degradação do solo manifestados na forma de compactação, erosão, perda da fertilidade, dentre outras, que comprometem a produção agrícola e consequentemente a manutenção das famílias assentadas, desse modo, constata-se a presença de atividades não agrícolas...
Keywords: Geografia; Assentamentos humanos - Bauru (SP); Assentamentos humanos - Pederneiras (SP); Solos - Fertilidade - Bauru (SP); Camponeses - Bauru (SP); Camponeses - Pederneiras (SP); Solos - Fertilidade - Pederneiras (SP); Geography